Designing Motorcycle Safety System Using Fingerprint Sensor, SMS Gateway, and GPS Tracker Based on ATMega328 - Situmorang, Marhaposan (Talenta Publisher, 2021)
A motorcycle security system has been designed using an ATMega328 microcontroller by applying fingerprint, SMS and GPS. The system consists of a GPS Module and a SIM Module. The system is designed to find the position of a stolen motorcycle via a Google Maps and create a security system on a motorcycle that uses a fingerprint sensor as a substitute for the key to turn on and turn off the motorcycle engine. ATMega328 is used as a processor, with additional GPS, GSM SIM 8000I, relay and buzzer. When a theft occurs, the system will send an SMS contained Google Maps link to the owner of the motorcycle. The results of the system design are expected to minimize the crime rate in motor vehicle theft cases.